Research on Optimization of Large Flow Hydraulic Punching Process in Zhaozhuang Mine - Jiabao Zhang; Dingqi Li (Geofluids)
Taking hydraulic punching test of Zhaozhuang Mine as engineering background, by comparing the field application effects of different hydraulic punching processes, the relationship between coal moisture content around the borehole blockage and gas extraction effect was monitored and analyzed. The following conclusions were drawn: the occurrence of borehole blockage was the result of the comprehensive action of coal slag particle size and slag discharge capacity of punching return water. Blocking the borehole led to the accumulation of a large amount of punching high-pressure water and coal slag in the borehole, which compressed and infiltrated the surrounding coal body and reduced gas extraction efficiency of borehole. Under the condition of the same amount of coal produced by punching, the different punching methods led to the great difference in the influence radius of punching. The large flow three-stage coal-breaking hydraulic punching system developed according to the borehole blockage mechanism can effectively reduce the particle size of coal slag, increase the punching flow, effectively avoid borehole blockage, and improve gas extraction efficiency of borehole.